EFFICACY OF A SOLVENT-FREE CRUDE EXTRACT OF LEMONGRASS (CYMBOPOGON CITRATUS) AND SUGAR APPLE (ANNONA SQUAMOSA) AS AN INSECT REPELLENT - Mangubat, Florieza M (Journal of Agriculture and Technology Management, 2022)
Essential oils of sugar apple and lemongrass are highly insect repellent ingredients due to their relatively low toxicity, comparable efficacy, and customer approval. Experimental research assessed the larvicidal ability of solvent-free combined crude extract of lemongrass and sugar apple under varied time intervals (5 minutes, 10 minutes, 15 minutes and 20 minutes). Findings showed that commercial spray is more effective against mosquito larvae versus the combined crude extract of lemongrass and sugar apple. However, combined lemongrass and sugar apple extract divulged potential larvicidal activity against dengue-causing mosquito vectors and need to be reformulated for greater concentrations to equate commercial mosquito spray effectiveness.